1997
DOI: 10.1359/jbmr.1997.12.3.384
|View full text |Cite
|
Sign up to set email alerts
|

An Intact N Terminus Is Required for the Anabolic Action of Parathyroid Hormone on Adult Female Rats

Abstract: Intermittent administration of parathyroid hormone (PTH) peptides increases bone density in animal and human models of osteoporosis. In vitro studies have demonstrated that PTH analogs lacking the first two amino acids can stimulate cell proliferation in certain cell systems, whereas fragments with an intact N terminus can be antimitogenic. We have tested whether the truncated PTH(3-38) fragment may be a better "anabolic analog" than PTH(1-38) by monitoring bone density and biomechanical properties of the femu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 59 publications
3
28
0
1
Order By: Relevance
“…Our studies demonstrate that osteoblast expression of Rs1, an engineered G s -coupled RASSL with constitutive G s activity, induces a dramatic anabolic bone effect that is significantly different from previous models (10)(11)(12)(13)(14)(15). The ColI(2.3)ϩ/Rs1ϩ mice display several unique and unexpected characteristics, including a crucial temporal requirement for Rs1 expression, an unusually large amount of bone mineral accrual, and effects on bone macroarchitecture.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Our studies demonstrate that osteoblast expression of Rs1, an engineered G s -coupled RASSL with constitutive G s activity, induces a dramatic anabolic bone effect that is significantly different from previous models (10)(11)(12)(13)(14)(15). The ColI(2.3)ϩ/Rs1ϩ mice display several unique and unexpected characteristics, including a crucial temporal requirement for Rs1 expression, an unusually large amount of bone mineral accrual, and effects on bone macroarchitecture.…”
Section: Discussionmentioning
confidence: 63%
“…Mice expressing a constitutively active PTHR1 in osteoblasts show increased trabecular bone volume and decreased cortical bone thickness at 12 weeks of age, with grossly normal femur shape and size (10,11). In addition, models using PTH peptide fragments that selectively activate PTHR1-linked G s signaling (12)(13)(14)(15) suggest that G s signaling can increase bone formation. Because a mouse model with constitutively active GNAS in osteoblasts has not been developed, the direct role of activated G s signaling in osteoblasts has not been clearly tested.…”
mentioning
confidence: 99%
“…However, despite this knowledge, the function of CREM factors in bone remains largely unknown. It is generally accepted that cAMP-mediated PKA activation through PTH1 receptors in osteoblasts is both necessary and sufficient for the anabolic effect of PTH in vivo (16,17), although the role of PKC activation cannot be excluded (25). Our previous initial pilot experiment did not reveal an obvious bone phenotype of Crem KO mice.…”
Section: Discussionmentioning
confidence: 77%
“…Cells of the osteoblast lineage contain PTH receptors and serve as the primary target cells of PTH signaling in bone (15). Although PTH activates both the cAMPprotein kinase A (PKA) and PKC pathways in osteoblasts, cAMP-PKA signaling has been shown to be critical for the anabolic effect of PTH on bone mass acquisition (16,17). It is shown that the time course of RANKL and OPG expression is different between acute and sustained PTH treatment in mice (18).…”
Section: Introductionmentioning
confidence: 99%
“…Daily injections of PTH(1-34) or PTH(1-31) produced an equivalent anabolic effect in rats; however, whereas PTH(1-34) activates both cAMP production and PKC, PTH (1-31) only activates cAMP production [41]. On the other hand, PTH(3-38), which activates PKC but not cAMP production, did not cause an anabolic effect [42]. Therefore, PTHstimulated cAMP production is sufficient for initiation of signaling cascades that increase osteoblast number, but activation of PKC is not.…”
Section: Osteoblast Specific Actions Of Pth Signaling Involved With Amentioning
confidence: 97%